2014
DOI: 10.1007/s00464-014-3558-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the technical difficulty and clinical outcome of endoscopic submucosal dissection for colorectal tumors

Abstract: Severe fibrosis contributed to both incomplete resection and difficult colorectal ESD. Larger tumor size and paradoxical movement during the procedure were independent factors contributing to the difficulty of colorectal ESD. These factors might enable endoscopists to develop strategies for treating colorectal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 29 publications
6
81
2
Order By: Relevance
“…Similar to our results, a previous study has reported that the presence of fibrosis was associated with difficult procedures and low complete resection rates during colorectal ESD 1215. When the degree of fibrosis was assessed, F2 fibrosis was associated with this outcome 12.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, a previous study has reported that the presence of fibrosis was associated with difficult procedures and low complete resection rates during colorectal ESD 1215. When the degree of fibrosis was assessed, F2 fibrosis was associated with this outcome 12.…”
Section: Discussionsupporting
confidence: 91%
“…Its advantages compared to surgery are its less invasive nature and its low rate of complications. However, ESD requires the performance of advanced endoscopic techniques, and it can cause intraoperative perforation and postoperative bleeding, with reported rates of 1-6 % and 1-2.4 %, respectively, on colonic ESD [25][26][27][28][29][30]. Rates reported for complete resection and curative resection for ESD are 84-87 % and 80-90 %, respectively [9,[30][31][32], which are considered acceptable.…”
Section: Discussionmentioning
confidence: 88%
“…reported that risk factors for incomplete resection while using colorectal ESD are SM deep invasion, unfavorable histological type at the deepest site of SM invasion, and a submucosal severe fibrosis . Recently, a similar report has also been published . At present, as the safety of colorectal ESD has already been established, high‐quality colorectal ESD needs to be developed.…”
Section: Problems With Esd As Total Excisional Biopsy For Ct1 Colorecmentioning
confidence: 85%